THE CONCEPT OF AL-RASIKHUNA FI AL-‘ILM A PERSPECTIVE OF AL-‘ALLAMAH AL-TABATABA’I IN THE BOOK OF AL-MIZAN - Abrar, Andi; Mahfudz, Muhsin; Sohrah, Sohrah (Program Pascasarjana, UIN Alauddin Makassar, 2020)
Allah reveals the Quran as a guidance to those who are pious and those who are not. In Quran, there are some verses that can be easily comprehended, also known as muhkam verses. There are also quite cryptic verses known as mutasyabih. The interpretation of the Quran often be divise, and divided into two groups. The first group derives and uses the mutasyabih verses of the Quran as a reason to spread deception and finding its takwil (original meaning) due to their heart prefers to the misguidance. The second group is them, whom they are the experts and is known as al-Rasikhuna fi al-‘ilm. They interpret the verses of the Quran, bith muhkam and mutasyabih, based on the opinion that all is coming from Allah. Understanding of the Quran making them more faithful, and therefore called as ulul albab. The term al-Rasikhuna fi al-‘ilm in Quran and hadith does not refer to a certain group or person. Hence, the interpretation of al-Rasikhuna fi al-‘ilm by the ulama depends on their mahzab.